MiR-138: A promising therapeutic target for cancer - Huan-Huan Sha; Dan-Dan Wang; Dan Chen; Si-Wen Liu; Zhen Wang; Da-Li Yan; Shu-Chen Dong; Ji-Feng Feng (Tumor Biology)
MicroRNAs are small noncoding RNAs which regulate gene expressions at post-transcriptional level by binding to the 3′-untranslated region of target messenger RNAs. Growing evidences highlight their pivotal roles in various biological processes of human cancers. Among them, miR-138, generating from two primary transcripts, pri-miR-138-1 and pri-miR-138-2, expresses aberrantly in different cancers and is extensively studied in cancer network. Importantly, studies have shown that miR-138 acts as a tumor suppressor by targeting many target genes, which are related to proliferation, apoptosis, invasion, and migration. Additionally, some researches also discover that miR-138 can sensitize tumors to chemotherapies. In this review, we summarize the expression of miR-138 on regulatory mechanisms and tumor biological processes, which will establish molecular basis on the usage of miR-138 in clinical applications in the future.